The HELIOS trial protocol: a Phase III study of ibrutinib in combination with bendamustine and rituximab in relapsed/refractory chronic lymphocytic leukemia. (January 2015) - Hallek, Michael; Kay, Neil E; Osterborg, Anders; Chanan-Khan, Asher A; Mahler, Michelle; Salman, Mariya; Wan, Ying; Sun, Steven; Zhuang, Sen Hong; Howes, Angela
ABSTRACT : Ibrutinib is an orally administered, covalent inhibitor of Bruton's tyrosine kinase with activity in B-cell malignancies based on Phase I/II studies. We describe the design and rationale for the Phase III HELIOS trial (trial registration: EudraCT No. 2012-000600-15; UTN No. U1111-1135-3745) investigating whether ibrutinib added to bendamustine and rituximab (BR) provides benefits over BR alone in patients with relapsed/refractory chronic lymphocytic leukemia/small lymphocytic lymphoma. Eligible patients must have relapsed/refractory disease measurable on CT scan and meet ≥1 International Workshop on Chronic Lymphocytic Leukemia criterion for requiring treatment; patients with del(17p) are excluded. All patients receive BR (maximum six cycles) as background therapy and are randomized 1:1 to placebo or ibrutinib 420 mg/day. Treatment with ibrutinib or placebo will start concomitantly with BR and continue until disease progression or unacceptable toxicity. The primary end point is progression-free survival. Secondary end points include safety, objective response rate, overall survival, rate of minimal residual disease-negative remissions, and patient-reported outcomes. Tumor response will be assessed using the International Workshop on Chronic Lymphocytic Leukemia guidelines.